DECISION SUPPORT SYSTEM FOR AUCTION OBJECT SELECTION WITH THE TOPSIS METHOD - ELIDA TUTI SIREGAR (STMIK KAPUTAMA, 2020)
The object of auction of mortgage rights is an immovable object as a collateral item that is guaranteed by the debtor to the creditor. In the auction process requires an auction object that has the potential to facilitate the execution of the auction object. Potential Auction Object selection will be a solution in determining which objects are more potential to be auctioned and provide space to more easily execute which objects must be done first. However, in selecting an auction object, it will certainly experience difficulties because each debtor has almost the same criteria as location, building specifications. The method used in making a decision on the potential auction object selection is TOPSIS. is a multi-criteria method that is used to identify solutions of alternative sets based on simultaneous minimization of the ideal point distance and maximize distance from the lowest point so it can facilitate decision making for auction objects that can be executed first.